Influence Of Quality Product And Brand Awareness Regarding Purchase Interest Of Eiger Products In Tasikmalaya - Maulana, Muhammad Gifarulfajri; Pauzy, Depy Muhamad; Yuniar, Evilia Sri (Utami Publisher, 2025)
This study aims to determine the effect of Product Quality and Brand Awareness on Purchase Interest in Eiger Products in Tasikmalaya. The method used is quantitative with a research sample of 100 respondents. The data used are primary and secondary data. The analysis tool used in this study is multiple linear regression analysis using SPSS version 26. Based on the results of this study, it shows that Product Quality and Brand Awareness simultaneously have a positive and significant effect on Purchase Interest in Eiger Products in Tasikmalaya. Product Quality partially has a significant effect on Purchase Interest. Brand Awareness has a significant effect on Purchase Interest.